Systematic review of strategies to increase access to health services among children over five in low‐ and middle‐income countries - Bright, T; Felix, L; Kuper, H; Polack, S (John Wiley & Sons Ltd, 2018)
Background The populations of many low‐ and middle‐income countries (LMIC) are young. Despite progress made towards achieving Universal Health Coverage and remarkable health gains, evidence suggests that many children in LMIC are still not accessing needed healthcare services. Delayed or lack of access to health services can lead to a worsening of health and can in turn negatively impact a child's ability to attend school, and future employment opportunities. Methods We conducted a systematic review to assess the effectiveness of interventions aimed at increasing access to health services for children over 5 years in LMIC settings. Four electronic databases were searched in March 2017. Studies were included if they evaluated interventions that aimed to increase: healthcare utilisation, immunisation uptake and compliance with medication/referral. Randomised controlled trials and non‐randomised study designs were included in the review. Data extraction included study characteristics, intervention type and measures of access to health services for children above 5 years of age. Study outcomes were classified as positive, negative, mixed or null in terms of their impact on access outcomes. Results Ten studies met the criteria for inclusion in the review. Interventions were evaluated in Nicaragua (1), Brazil (1), Turkey (1), India (1), China (1), Uganda (1), Ghana (1), Nigeria (1), South Africa (1) and Swaziland (1). Intervention types included education (2), incentives (1), outreach (1), SMS/phone call reminders (2) and multicomponent interventions (4). All evaluations reported positive findings on measured health access outcomes; however, the quality and strength of evidence were mixed. Conclusion This review provides evidence of the range of interventions that were used to increase healthcare access for children above 5 years old in LMIC. Nevertheless, further research is needed to examine each of the identified intervention types and the influence of contextual factors, with robust study designs. There is also a need to assess the cost‐effectiveness of the interventions to inform decision‐makers on which are suitable for scale‐up in their particular contexts.